STUDY ON THE MORPHOLOGY AND FUNCTION OF ADIPOSE TISSUE IN DIABETIC PATIENTS (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate the correlation between adipose tissue morphology, assessed by percent body fat, and adipose tissue function, assessed by the visceral adiposity index, with poor glycemic control in patients with diabetes mellitus.Methods: A descriptive cross-sectional study with analytical components was conducted on 90 patients diagnosed with diabetes according to the ADA (2025) criteria at the Outpatient Department, University Medical Center Ho Chi Minh City - Campus 2. Poor glycemic control was defined as HbA1c ≥ 7.0%. Correlations were assessed using Spearman’s correlation test.Results: Participants in this study were relatively older, with a median age of 66 years. Approximately 58% of patients had poor glycemic control. Visceral adiposity index showed a weak correlation with fasting plasma glucose (rho = 0.207), and moderate correlations with HbA1c (rho = 0.308) and overall glycemic control status (rho = 0.322). In contrast, percent body fat demonstrated only a weak correlation with fasting plasma glucose (rho = 0.221, p < 0.05).Conclusion: Most patients in the study exhibited abnormalities in both adipose tissue morphology and function, as reflected by higher percent body fat and visceral adiposity index values compared to previous studies. Both visceral adiposity index and percent body fat were significantly associated with blood glucose levels and glycemic control status.
Keywords: Percent body fat (PBF), visceral adiposity index (VAI), type 2 diabetes mellitus, diabetes management, overweight and obesity.